Center za zaslužne profesorje in upokojene visokošolske učitelje Univerze v Mariboru: 2019–2023 (University of Maribor Press, 2023)
Center for Emeritus Professors and Retired Higher Education Teachers of the University of Maribor: 2019–2023. The publication presents various areas of activity of the Centre in the period between 2019 and 2023. The Centre promoted intergenerational solidarity by recognizing heterogeneity and diversity within and between age groups, cooperation, and social cohesion. The collected contributions follow the mission of the Centre, which is aimed at e-learning and e-education, care for health, innovative, sustainable, and socially responsible development of the environment, and showing the needs of an aging society, which enables active aging and raising the quality of life of the elderly. The operation of the Centre is harmonized with the goals and principles of age-friendly universities. The contributions present various professional and intergenerational perspectives on current social events, which are of key importance for the development of a humane, democratic society. Art and culture are indispensable companions of life, especially in the mature age, when the need to enjoy art usually increases, so a contribution about art in the period of maturity and a set of memoirs that enrich our work are also valuable. The publication is complemented by works from the late oeuvre of emeritus professor Bojan Golija (1932–2014).